Revealed preferences for climate protection when the purely individual perspective is relaxed: Evidence from a framed field experiment - Andreas Löschel; Bodo Sturm; Reinhard Uehleke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
In this paper, we investigate the real demand for climate protection when the purely individual perspective of existing revealed preference studies is relaxed. This is achieved in two treatments; first, we determine the information subjects receive about the demand revealed by other subjects in a similar decision making situation, second, collective action is implemented whereby all subjects are required to purchase the group's median quantity at a given price. Participants in the experiment were offered the opportunity to contribute to climate protection by purchasing European Union Allowances. Allowances purchased were withdrawn from the European Emissions Trading Scheme. In our experiment, information about other subjects' behaviour has no treatment effect on the demand for climate protection. Under collective action however, the probability of purchasing allowances is higher compared to the reference treatment situation, an individual contribution mechanism. Furthermore, we observe a strong correlation between subjects' demand and their expectations about other participants' behaviour. When collective action is not available, subjects' expectations are consistent with free rider behaviour.
urn:nbn:de:bsz:180-madoc-331662
Keywords: Q51; Q54; C93; 330; experimental economics; demand for climate protection; climate change; willingness to pay